Classification of cubic auxetics. Issue 10 (4th September 2013) - Goldstein, Robert V.; Gorodtsov, Valentin A.; Lisovenko, Dmitry S.
<x xml:space="preserve">Abstract</x> Two‐parameter analysis of auxetics among the cubic crystals is proposed. A brief analysis of the equivalence of this two‐parameter consideration and other approaches is given. The main result of this paper is the classification of partial auxetics with a single dimensionless complex, which is composed of the crystals elastic compliances. The auxetic surface separates the regions with negative and positive Poisson's ratio. The character of its changes with change of the dimensionless complex is determined. The critical value of the complex where a topological rearrangement of the auxetic surface occurs is obtained. The distribution of partial auxetics in zones with different values of the dimensionless complex was found. The sign of another dimensionless parameter influences the location of a region with negative Poisson's ratio relative to the auxetic surface. <inline-graphic xlink:href="ark:/27927/pgg3jzfwzht" content-type="pssb201384233-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> View of the auxetic boundary for a cubic crystal when the dimensionless elastic parameter is close to the critical value <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzfxm0v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Πc≈0.745</alternatives>.